Predictors and outcome of patients with acute respiratory distress syndrome caused by miliary tuberculosis: a retrospective study in Chongqing, China - Deng Wang (BMC Infectious Diseases, 2012)
Abstract Background Miliary tuberculosis (TB) is an uncommon cause of acute respiratory distress syndrome (ARDS) with a high mortality. The aim of the present study was to evaluate the clinical characteristics, predictors and outcome of patients with ARDS caused by miliary TB. Methods A retrospective study was conducted among patients with a diagnosis of ARDS with miliary TB in four hospitals from 2006 to 2010. Medical records and laboratory examinations of these patients were taken during the first 24 h of admission. Results Eighty-five patients with miliary TB developed ARDS, 45 of whom survived (52.9%). The median age was 36.6 ± 12.5 years with 38 males (44.7%). Diabetes mellitus (DM) was the most common underlying disease (18.8%).ICU mortality was 47.1%. The time from admission to anti-tuberculosis therapy was 4.5 ± 2.0 days. Mean duration of mechanical ventilation was 8.5 ± 3.0 days in all patients. Duration of time to diagnosis, time from diagnosis to mechanical ventilation, and time to anti-tuberculosis therapy were significantly shorter in survivors than those in non-survivors. Diabetes mellitus (OR 5.431, 95%CI 1.471-20.049; P = 0.005), ALT (70-100U/L, OR 10.029, 95%CI 2.764-36.389; P = 0.001), AST (>94U/L,OR 8.034, 95%CI 2.200-29.341; P = 0.002), D-dimer (>1.6mg/L, OR 3.167, 95%CI 0.896-11.187; P = 0.042), hemoglobin (<90g/L, OR 14.824, 95%CI 3.713-59.179; P = 0.001), albumin (<25g/L, OR 15.896, 95%CI 3.975-63.566; P = 0.001) were independent predictors of ARDS development in the setting of miliary TB. Conclusions Accurate diagnosis, early initiation of anti-tuberculosis therapy and mechanical ventilation are important for the outcome of patients with ARDS caused by miliary TB. DM, ALT, AST, D-dimer, hemoglobin, and albumin are independent predictors of ARDS development in patients with miliary TB.